Managerial decision making in indicating a disruption of critical infrastructure element resilience - Alena Splichalova; David Patrman; Nikol Kotalova; Martin Hromada (Administrative Sciences, 2020)
Managerial decision making is an integral process used in public and private organizations. Critical infrastructure entities are a strategically significant group dependent on the quality of decision-making processes. They aim to provide services necessary to ensure state security and to satisfy basic human needs. The quality of decision making is an important factor in the management of these entities. The quality level is determined by many factors, the key of which is risk management. For this reason, it is necessary for the operators to minimize risks affecting the elements of the critical infrastructure through which these services are provided. Risk management is commonly used for this purpose, making it possible to assess and manage these risks. However, there is a specific group of threats that affects the resilience of these elements. The indication of these threats is not possible through common risk management. Therefore, it is necessary to develop specific scenarios of negative impacts and procedures for assessing their impact on the resilience of elements of the critical infrastructure. To this end, this conceptual article introduces an entirely new managerial decision-making process for indicating the resilience of critical infrastructure elements.
Keywords: 350; managerial process; decision making; critical infrastructure elements; resilience; disruption; indication